Findings supporting neonatal screening for sickle cell disease: an observational study in Senegal - Petigas, Lucie; Seck, Ndiogou; Doupa, Dominique; Diagne, Ibrahima; Roth-Kleiner, Matthias (Frontiers in Pediatrics, 2025)
IntroductionSickle cell disease (SCD) is a major contributor to morbidity and mortality in sub-Saharan Africa, and early detection through neonatal screening can improve outcomes. In Senegal, systematic screening is not yet implemented. This study describes two cohorts of children diagnosed with SCD: those identified through neonatal screening and those diagnosed clinically after presenting symptoms.MethodsThis retrospective study involved two cohorts of children diagnosed with SCD in St. Louis, Senegal, between 2010 and 2020—one through neonatal screening (A) and the other clinically (B). Epidemiological, clinical, and management data were analyzed.ResultsCohort A included 17,083 screened infants (74% screening rate), with 40 diagnosed at a mean age of 70.48 days, showing low complication rates and requiring less intensive treatment. Cohort B, with 39 clinically diagnosed children, had a mean diagnosis age of 21.9 months, with higher rates of hospitalizations, transfusions, and acute anemia. Vaccination and antibiotic prophylaxis were high in both cohorts.DiscussionNeonatal screening enables early diagnosis, reducing complications and enabling timely interventions, while children diagnosed after symptoms face more severe disease. Early genetic counseling and addressing consanguinity are key for better outcomes. Challenges such as limited funding, equipment, and trained personnel must be addressed for broader implementation.ConclusionNeonatal screening aligns with public health goals by reducing morbidity and mortality, and the long-term economic burden on families and healthcare systems. It is particularly relevant in the context of increasing global migration patterns, underscoring the need for such programs worldwide.